Optimalisasi Peran Komite Madrasah dalam Peningkatan Mutu Pendidikan di MA Babulkhair Bongkudai - Susanti, Ressi (ETIC (EDUCATION AND SOCIAL SCIENCE JOURNAL), 2025)
This research is motivated by the importance of the madrasah committee's role as a strategic partner in improving educational quality. A preliminary study at MA Babulkhair Bongkudai indicates that the madrasah committee has not optimally performed its role, tends to be considered merely administrative complement, and faces various operational constraints. This study aims to analyze the implementation of the madrasah committee's roles as an advisory, supporting, controlling, and mediating body, as well as to identify factors affecting the effectiveness of these roles. The research employs a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation. Research informants include the principal, committee chairman, and purposively selected teachers. Data analysis utilizes an interactive model with source and technique triangulation to ensure data validity. The findings reveal that the madrasah committee's roles vary in their effectiveness. The advisory and supporting roles have functioned adequately, however, the controlling role remains suboptimal and the mediator function is limited to internal communication. Supporting factors include harmonious communication and transparency from the madrasah management, while inhibiting factors include limited human resources, time constraints, and weak coordination among committee members. The research concludes that there is a need for paradigm transformation and capacity building of the madrasah committee through the development of technology-based management systems, enhancement of member competencies, and strengthening of cooperation networks to optimize the committee's role in improving educational quality.